Analisis Kebutuhan dan Perancangan Sistem Informasi Evaluasi Risiko Psikososial Pekerja: Studi Kasus Kementerian Ketenagakerjaan Republik Indonesia - Erasto Akbar Adjie; Betty Purwandari (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
The Ministry of Manpower of the Republic of Indonesia has operated a psychosocial risk evaluation information system (V1) across 19 companies in six industrial sectors, yet a three-level evaluation covering interface assessment, source-code review, and stakeholder interviews revealed persistent gaps in data security, role differentiation, dynamic reporting, and interoperability with the national occupational safety and health ecosystem. This study aims to identify the functional and non-functional requirements needed to address these gaps and to develop a system design that supports integration with the national digital platform. An incremental development approach with a software-evolution entry point, situated within a design science research framework, was adopted. The study produced eleven change proposals, ten functional and eight non-functional requirements, and a design comprising a six-module architecture, twelve database tables, ten high-fidelity interfaces, seven API endpoints, and seventeen behavioral diagrams. Stakeholder validation confirmed the relevance of the design concepts and surfaced six substantive refinements for the next iteration. Thereby, contributing to the technical basis for national implementation of Ministerial Regulation No. 5 of 2018 on Occupational Safety and Health in the Work Environment, which mandates psychosocial factor monitoring across Indonesian companies.